Depressive symptoms among older adults with diabetes mellitus: a cross-sectional study - Andrade, Diego Micael Barreto; Rocha, Roseanne Montargil; Ribeiro, Icaro José Santos (São Paulo Medical Journal, 2023)
BACKGROUND: Diabetes mellitus is a chronic disease with long-term consequences that is often associated with depressive symptoms. This relationship predicts increased morbidity and mortality rates, leading to serious health consequences. OBJECTIVE: To identify the prevalence and health factors associated with depressive symptoms among older adults with diabetes mellitus. DESIGN AND SETTING: An observational cross-sectional study was conducted among 236 older adults in the Basic Healthcare Units of Jequié, Brazil. METHODS: A survey containing sociodemographic, behavioral, and health conditions was used as a data collection instrument, in addition to the Geriatric Depression Scale. The main inclusion criterion was older adults diagnosed with diabetes mellitus. To identify the risk factors associated with depressive symptoms among older adults with diabetes mellitus, logistic regression analysis was conducted for calculating the odds ratio (OR), and a 95% confidence interval (CI) was considered statistically significant. RESULTS: The prevalence of depressive symptoms was 24.2% among older adults with diabetes, corroborating the Brazilian average of 30%. The final multivariate analysis model for the risk of depressive symptoms showed a significant association with diabetes complications [OR = 2.50, 95% CI 1.318–4.74)] and osteoporosis [OR = 2.75, 95% CI 1.285–5.891)]. CONCLUSION: A high prevalence of depressive symptoms was observed among older adults with diabetes. Critically examining older adults with diabetes mellitus is necessary, and screening for depressive symptoms is highly recommended, especially for those with complications resulting from diabetes mellitus and musculoskeletal comorbidities, such as osteoporosis, as it seems to be associated with depressive symptoms.